Factors associated with death in patients with COVID-19 admitted to the Adult Intensive Care Unit - Gabriela Müller Generoso; Catiele Raquel Schmidt; Edna Ribeiro de Jesus; Julia Estela Willrich Boell; Greici Capellari Fabrizzio; Michelle Mariah Malkiewiez; Elisiane Lorenzini (Universidade Federal do Ceará, 2024)
Objective: to identify factors associated with death in patients diagnosed with COVID-19 admitted to an intensive care unit. Methods: cross-sectional study with patients admitted with COVID-19 to two Intensive Care Units of two public hospitals. Data were collected from 222 electronic medical records and analyzed using Student's t-test, Fisher's exact test, Pearson's chi-squared test, and Poisson multiple regression with robust variance. Results: male patients prevailed, with a mean age of 63.4±15.6 years, white (92.9%), married or with a partner (64.6%), with elementary school education (64.4%). The factors that significantly impacted the outcome of death with the highest prevalence ratio were: dyspnea with respiratory effort (p=0.009), pulmonary involvement-CT pattern above 75% (p=0.006), acute renal failure requiring hemodialysis (p=0.001) and patients over 65 years of age (p=0.001). Conclusion: age was identified as the main independent factor for death. Contributions to practice: knowing the characteristics of hospitalizations in critical care units of patients with COVID-19 provides support for providing qualified nursing care, promoting patient safety.